The hidden girl / A True Story of the Holocaust - Kaufman Rein Lola 1934-; Lola Rein Kaufman (New York : Scholastic, 2010)
After deciding to donate the dress her mother had made for her to a museum, Lola Rein Kaufman, survivor of the Nazi Holocaust, decides that it is finally time to speak publicly about her experiences.
M
750